Potensi Batugamping Untuk Bahan Baku Industri Semen Daerah Biluhu Timur Dan Sekitarnya - Destira Handayani Eksan; Ahmad Zainuri; Muhammad Kasim (Jambura Geoscience Review, 2019)
Limestone is a sedimentary rock composed by calcium carbonate derived from the rest of marine organisms and the main materials of cement so exploration and calculation of limestone resources need to be done. The research area is administratively located at the Biluhu Timur Village and its surroundings, Batudaa Pantai District, Gorontalo Regency. The purpose of this study is to observe the geological conditions of the study area to determine distribution of limestones in the study area to be used as cement industrial materials with the geological mapping, and the analysis limestone geochemical using XRF (X-Ray Flourescence). Based on the result of this research can be concluded that the research area was devided into four geomorphological units, consisting of volcanic hills unit, denudational hills and plain unit, and the coastal plain unit. The litology arranged by granodiorit, basal, and the limestone (packstone and wackestone). Based on the result of geochemical analysis using XRF and calculation of volume using Surpac softwere can be devided into three blocks. The A block have limestones (packstone) with the content of CaO 51.79% and MgO 1.98% that meets the requirement materials of portland cement with total volume 423 107 230 tons. The B block have limestones (wackestone) with the content of CaO 4.92% and MgO 5.28% that not meets the requirement materials of portland cement with total volume 729 263 008 tons. The C block have limestones (packstone) with the content of CaO 52.85% and MgO 0.98% that meets the requirement materials of portland cement with total volume 539 883 150 tons.